2022
DOI: 10.1021/acsomega.1c05640
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Combustion Methods on NOx Emissions from Co-combustion of Various Tannery Wastes

Abstract: To further increase combustion efficiency and reduce nitrogen oxide pollution caused by tannery wastes, three raw materials, including tannery sludge, chrome-tanned buffing dust, and chrome shavings, were burned together in a dual-bed model reactor under various conditions. In addition, a thermogravimetric analysis of co-combustion of three tannery wastes was studied in this study, which was conducive to understanding the combustion characteristics and positive effects. The comprehensive combustibility index S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…As an industrial waste, leather has a high organic matter content, and its direct combustion will cause serious pollution to the environment; therefore, the sustainable treatment of industrial waste is particularly important (Muralidharan et al 2022). Zhang et al (2022) studied the co-combustion process of tannery waste and found that parameters such as integrated combustion index and stable combustion characteristics index were increased, which indicated that effective combustion was achieved through co-combustion. Kluska et al (2020) studied the co-combustion of pelletized leather tannery waste and hardwood pellets on a grate.…”
Section: Introductionmentioning
confidence: 99%
“…As an industrial waste, leather has a high organic matter content, and its direct combustion will cause serious pollution to the environment; therefore, the sustainable treatment of industrial waste is particularly important (Muralidharan et al 2022). Zhang et al (2022) studied the co-combustion process of tannery waste and found that parameters such as integrated combustion index and stable combustion characteristics index were increased, which indicated that effective combustion was achieved through co-combustion. Kluska et al (2020) studied the co-combustion of pelletized leather tannery waste and hardwood pellets on a grate.…”
Section: Introductionmentioning
confidence: 99%
“…Urea can also be applied in its pure, solid form. Two processes are important for the removal of nitrogen from flue gases: SNCR and SCR [45].…”
mentioning
confidence: 99%